The role of pyroptosis in cancer: key components and therapeutic potential - Zixi Liu; Simiao Xu; Lin Chen; Jun Gong; Min Wang (Cell Communication and Signaling)
Abstract Pyroptosis is a lytic and inflammatory form of gasdermin protein-mediated programmed cell death that is typically initiated by inflammasomes. The inflammasome response is an effective mechanism for eradicating germs and cancer cells in the event of cellular injury. The gasdermin family is responsible for initiating pyroptosis, a process in which holes are made in the cell membrane to allow inflammatory chemicals to escape. Mounting evidence indicates that pyroptosis is critical for controlling the development of cancer. In this review, we provide a general overview of pyroptosis, examine the relationship between the primary elements of pyroptosis and tumors, and stress the necessity of pyroptosis-targeted therapy in tumors. Furthermore, we explore its dual nature as a double-edged sword capable of both inhibiting and facilitating the growth of cancer, depending on the specific conditions. Ultimately, pyroptosis is a phenomenon that has both positive and negative effects on tumors. Using this dual impact in a reasonable manner may facilitate investigation into the initiation and progression of tumors and offer insights for the development of novel treatments centered on pyroptosis.